PERUBAHAN BUNYI FONEM VOKAL ETIMON-ETIMON PROTOAUSTRONESIA DALAM BAHASA INDONESIA - Fredy Andrian, Fery (Humanis, 2015)
This study focused on changes in the sound etymon-etymon Proto- Austronesian in Indonesian. The purpose of this study is (1) knowing vowel phonemes sound changes that occur in etymon-etymon Proto-Austronesian languages in Indonesian; (2) determine the types of changes contained in the sound etymon-etymon Proto-Austronesian languages in Indonesian. The data in this study were analyzed by using the theory of sound law. Methods and techniques used in this study refer to the methods involved are competent and capable and involved free techniques noted in the data acquisition, data analysis performed by the method of comparison, data analysis and presentation of results delivered by formal and informal methods. Through, this study obtained sound linkage between Proto-Austronesian and Indonesian are detailed as follows. Some Proto-Austronesian phonemes derived linear, ie vowels */ i /. Proto- Austronesian phonemes derived with the change, namely the phoneme */ u / decrease the phoneme / o / and / ? /, */ e / decrease the phoneme / a / and / ? /, */ ? / decrease the phoneme / a /, */ ? / decrease the phoneme / a /, found several types of sound change, namely: dissimilation, syncope, apokop, aferesis, epentesis, protesis, metathesis, and palatalization.
Keywords: sound change, meaning change, Proto - Austronesian, Indonesian